A Mendelian randomization study investigating causal links between gut microbiota or metabolites and chronic hepatitis B - Xing, Tongjing; Wang, Xuequan; He, Shanshan (Frontiers in Public Health, 2024)
Objective: This study aimed to explore the potential causal relationship between the gut microbiota and/or its metabolites and the progression of chronic hepatitis B(CHB). Method: The gut microbiota was used as the exposure factor. The training set exposure data were obtained from the China Nucleotide Sequence Archive(CNSA). Genome-wide association study(GWAS) data from Asia were used as the outcome variables.Outcome data for both the training and validation sets were sourced from the GWAS Catalog database. A dual-sample Mendelian randomization approach was used to analyze the causal relationships, with the inverse variance-weighted method serving as the main analytical strategy. Sensitivity analysis was conducted to assess the robustness of Mendelian randomization analysis results. Result: In the training set database, analysis using the inverse variance-weighted method revealed a positive correlation between Fusobacterium varium and chronic hepatitis B [OR = 1.122, 95% CI (1.016, 1.240), P = 0.022]. Conversely, Veillonella parvula exhibited a negative correlation with chronic hepatitis B [OR = 0.917, 95% CI (0.852, 0.987), P = 0.021]. Sensitivity analysis revealed no evidence of pleiotropy and heterogeneity. No gut microbiota metabolites with a causal effect on chronic hepatitis B were identified. Additionally, no associations between the gut microbiota and the progression of chronic hepatitis B were found in the validation data from the European cohort. Conclusion: This study suggests that F. varium may facilitate the progression of chronic hepatitis B, whereas V. parvula may impede it. No causal relationships between gut microbiota metabolites and chronic hepatitis B were established.